Perancangan Mebel Multifungsi untuk Apartemen SOHO di Surabaya - Nasthasia Alyssa Buwana (Intra, 2016)
In this day and age, the less land available, but the demand for space is increasing. Humans tried to live as efficiently and effectively as possible both in terms of cost, space and energy. The Apartments is now present with the concept of SOHO, which can be used as an office or residence. To be able to use space as effectively and efficiently as possible, multi-functional furniture is needed to accommodate the living and working activity yet user-friendly and convenient to use. Adopting the design method according to Campbell, the design is through four stages, namely, Empathize (data data collecting through the literature and interviews), Define (the preparation and processing of data), Ideate (excavation design ideas and making a sketch of design as well as alternative), and Prototype (prototype to determine the shortcomings of the design). The design results in the form of 9 pieces of multifunctional furniture that accommodates the needs of the activity live and work. The furnishings are an amalgamation desks and mattresses, kitchen sets and dining table, as well as a work desk and table tv.